Interdisciplinary management of acute ischaemic stroke: Current evidence training requirements for endovascular stroke treatment. Position Paper from the ESC Council on Stroke and the European Association for Percutaneous Cardiovascular Interventions with the support of the European Board of Neurointervention - Nardai, Sandor; Lanzer, Peter; Abelson, Mark; Baumbach, Andreas; Doehner, Wolfram; Hopkins, L Nelson; Kovac, Jan; Meuwissen, Martijn; Roffi, Marco; Sievert, Horst; Skrypnik, Dmitry; Sulzenko, Jakub; et al. (European heart journal, 2021)
This ESC Council on Stroke/EAPCI/EBNI position paper summarizes recommendations for training of cardiologists in endovascular treatment of acute ischaemic stroke. Interventional cardiologists adequately trained to perform endovascular stroke interventions could complement stroke teams to provide the 24/7 on call duty and thus to increase timely access of stroke patients to endovascular treatment. The training requirements for interventional cardiologists to perform endovascular therapy are described in details and should be based on two main principles: (i) patient safety cannot be compromised, (ii) proper training of interventional cardiologists should be under supervision of and guaranteed by a qualified neurointerventionist and within the setting of a stroke team. Interdisciplinary cooperation based on common standards and professional consensus is the key to the quality improvement in stroke treatment.
Keywords: výsledek terapie; ischemická cévní mozková příhoda; Endovascular Procedures; Acute ischaemic stroke; Ischemic Stroke; endovaskulární výkony; cévní mozková příhoda; trombektomie; Stroke; ischemie mozku; Training requirements; Treatment Outcome; Carotid stenting; Interventional cardiology; lidé; Humans; Endovascular; Neurointervention; Thrombectomy; Brain Ischemia